Diagnostic laboratory standardization and validation of platelet transmission electron microscopy. (18th August 2018) - Chen, Dong; Uhl, Cindy B.; Bryant, Sandra C.; Krumwiede, Marcy; Barness, Ryan L.; Olson, Mary C.; Gossman, Susan C.; Erdogan Damgard, Sibel; Gamb, Scott I.; Cummins, Lisa A.; Charlesworth, Jon E.; Wood-Wentz, Christina M.; et al.
Abstract: Platelet transmission electron microscopy (PTEM) is considered the gold standard test for assessing distinct ultrastructural abnormalities in inherited platelet disorders (IPDs). Nevertheless, PTEM remains mainly a research tool due to the lack of standardized procedures, a validated dense granule (DG) count reference range, and standardized image interpretation criteria. The aim of this study was to standardize and validate PTEM as a clinical laboratory test. Based on previously established methods, we optimized and standardized preanalytical, analytical, and postanalytical procedures for both whole mount (WM) and thin section (TS) PTEM. Mean number of DG/platelet (plt), percentage of plts without DG, platelet count (PC), mean platelet volume (MPV), immature platelet fraction (IPF), and plt light transmission aggregometry analyses were measured on blood samples from 113 healthy donors. Quantile regression was used to estimate the reference range for DG/plt, and linear regression was used to assess the association of DG/plt with other plt measurements. All PTEM procedures were standardized using commercially available materials and reagents. DG interpretation criteria were established based on previous publications and expert consensus, and resulted in improved operator agreement. Mean DG/plt was stable for 2 days after blood sample collection. The median within patient coefficient of variation for mean DG/plt was 22.2%; the mean DG/plt reference range (mid-95th %) was 1.2–4.0. Mean DG/plt was associated with IPF ( p = .01, R 2 = 0.06) but not age, sex, PC, MPV, or plt maximum aggregation or primary slope of aggregation ( p > .17, R 2 < 0.02). Baseline ultrastructural features were established for TS-PTEM. PTEM was validated using samples from patients with previously established diagnoses of IPDs. Standardization and validation of PTEM procedures and interpretation, and establishment of the normal mean DG/plt reference range and PTEM baseline ultrastructural features, will facilitate implementation of PTEM as a valid clinical laboratory test for evaluating ultrastructural abnormalities in IPDs.